The temperature threshold for the transformation of rutin to quercetin in Tartary buckwheat dough. (15th June 2019) - Germ, Mateja; Árvay, Július; Vollmannová, Alena; Tóth, Tomáš; Golob, Aleksandra; Luthar, Zlata; Kreft, Ivan
Highlights: In non-treated Tartary buckwheat flour, most of the rutin was extracted in 20 min. By hydrothermal treatments at 25, 40 and 60 °C, most of the rutin was degraded. After hydrothermal treatments at 80 and 95 °C, rutin was retained in flour. Buckwheat flour-water mixture produced at 95 °C contained 12 mg rutin/g dry matter. Abstract: The aim was to determine conditions under which rutin can be retained during production of Tartary buckwheat ( Fagopyrum tataricum ) dough. Tartary buckwheat flour was hydrothermally treated by mixing with water at 25, 40, 60, 80 and 95 °C, with unprocessed Tartary buckwheat flour as control. With hydrothermal treatments at 25, 40 and 60 °C, most of the rutin was transformed to quercetin. However, for hydrothermal treatments at 80 and 95 °C, rutin was retained due to denaturation of the rutin-degrading enzymes during hydrothermal treatment. This is the first report to describe a temperature threshold for denaturation of rutin-degrading enzymes in any buckwheat material. Tartary buckwheat dough produced at 95 °C contained 12 mg rutin/g dry matter. Based on these characteristics, dough from hydrothermally treated Tartary buckwheat is a promising, rutin-rich functional food material.